INFLUENCE OF TRANSFORMATIONAL LEADERSHIP TO ORGANIZATIONAL LEARNING AMONG INDONESIA VOCATIONAL SCHOOL (THE ROLE OF DYNAMIC CAPABILITY) - Sundusiah Sundusiah; Agus Rahayu; Lili Adi Wibowo (Dinasti International Journal of Education Management And Social Science, 2021)
Organizational learning can be applied in companies and organizations, including vocational schools (SMK). The existence of Vocational Schools at this time has to provide maximum contribution in the provision of quality human resources. For this reason, continuous learning is needed to be able to increase its competitive advantage. This study aims to examine the effect of examinesl leadership and dynamic capability on organizational learning in Vocational High Schools (knowledgeIndonesia. The analytical technique used in this research is partial least square (PLS-SEM). The population in this study are 358 SMK in West Java Province, Indonesia. The intended respondent is the Principal of the SMK. The results of this study reveal that there is a positive influence either directly or through mediation of the variables studied othe n organizational learning.